Effect of ischemic compression for cervicogenic headache and elastic behavior of active trigger point in the sternocleidomastoid muscle using ultrasound imaging. Issue 4 (October 2017) - Jafari, Mehdi; Bahrpeyma, Farid; Togha, Mansoureh
Abstract : Abstract Objectives: To investigate the effect of ischemic compression on clinical outcomes of a cervicogenic headache and elastic behavior of myofascial trigger points. Design: Randomized, controlled trial. Setting: Outpatient headache clinic. Subjects: 19 subjects with a cervicogenic headache originating from myofascial trigger point within the sternocleidomastoid muscle. Interventions: Subjects were randomized in treatment group (n = 9) and control group (n = 10). Subjects in the treatment group received 4 sessions of ischemic compression in the myofascial trigger point region. Main measures: Headache intensity, frequency, and duration, trigger point elastic modulus, trigger point area, pressure tolerance, and pressure pain threshold were assessed before and after treatment. Results: Subjects in the treatment group compared with those in control group showed significant improvements in headache intensity (P = 0.002), headache frequency (P = 0.005), headache duration (P = 0.015), pressure tolerance (P < 0.001), pressure pain threshold (P = 0.039), and myofascial trigger point area (P = 0.017). Changes in myofascial trigger point elastic modulus did not reach a significant level (P > 0.05). Conclusion: The improvements in outcome measures suggest that ischemic compression may be effective in subjects with a cervicogenic headache associated with a myofascial trigger point in the sternocleidomastoid muscle. Data suggests that biomechanical properties of MTrP and severity of headache symptoms are not directly linked, and other mechanisms could be more influential in contributing to symptoms.